2003
DOI: 10.1021/la0349673
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Water in the Vicinity of Phospholipid Analogue Copolymers As Studied by Vibrational Spectroscopy

Abstract: The structure and hydrogen bonding of water in the vicinity of phospholipid analogue random copolymers [poly(2-methacryloyloxyethyl phosphorylcholine-r-n-butyl methacrylate), Poly(MPC-r-BMA)] with various molecular weights were analyzed in their aqueous solutions and thin films with contours of O−H stretching of Raman and attenuated total reflection infrared (ATR-IR) spectra, respectively. The relative intensity of the collective band (C value) corresponding to a long-range coupling of O−H stretchings of the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
120
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 144 publications
(127 citation statements)
references
References 62 publications
6
120
1
Order By: Relevance
“…Apparently, water plays a crucial role in modulating the interactions between PEO-and PC-enriched surfaces and proteins. 23,24 Comparison of PEO-and PC-based systems with respect to their effectiveness in preventing protein adsorption has been reported previously. 25 Silicon ͑Si͒ surfaces grafted with oligo͑ethylene glycol͒ methyl ether methacrylate ͑OEGMA͒ and 2-methacryloyloxyethyl phosphorylcholine ͑MPC͒, which contain, respectively, PEO and PC sidechains of comparable size, were chosen as the basis for this comparison.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Apparently, water plays a crucial role in modulating the interactions between PEO-and PC-enriched surfaces and proteins. 23,24 Comparison of PEO-and PC-based systems with respect to their effectiveness in preventing protein adsorption has been reported previously. 25 Silicon ͑Si͒ surfaces grafted with oligo͑ethylene glycol͒ methyl ether methacrylate ͑OEGMA͒ and 2-methacryloyloxyethyl phosphorylcholine ͑MPC͒, which contain, respectively, PEO and PC sidechains of comparable size, were chosen as the basis for this comparison.…”
Section: Introductionmentioning
confidence: 91%
“…The highly hydrated layer associated with the PC headgroups is believed to result in decreased protein adsorption and improved biocompatibility. 22 Recently, using polarized Raman and attenuated total reflection infrared spectroscopies, Kitano et al 23,24 investigated the hydrogen-bond network structure of the water molecules in the vicinity of various watersoluble polymers and calculated the number of hydrogen bonds per monomer unit in the water which are "collapsed" ͑N collapsed ͒ by the presence of polymer. They found that in the case of PEO-and PC-containing polymers, N collapsed is practically zero and much smaller than for other polymers, suggesting that PEO-and PC-containing polymers do not significantly disturb the hydrogen bonding between water molecules.…”
Section: Introductionmentioning
confidence: 99%
“…18) The q values were expressed as the mean of 15 portions of the polymer surface and expressed as the meanϮstandard error (S.E.) of three independent polymer films.…”
Section: Measurement Of Contact Angle Of Air Bubblesmentioning
confidence: 99%
“…In this regard, dynamics of water should be considered in order to realize zero protein adsorption surface. Some reports have attempted to clarify hydration state, and it was revealed that hydration state at the surface has strong effect on protein adsorption [3][4][5][6][7][8]. Among them, Ishihara et al clearly demonstrated that the hydrophilic polymer surfaces with high-free water fraction reduced protein adsorption.…”
Section: Introductionmentioning
confidence: 99%